Respon Petani Terhadap Pengembangan Tanaman Sorgum Pada Kelompok Tani Sinar Harapan - Anjelina Palang; Gabriel Otan Apelabi; Taras Iawan Saputera Wanda (Agriculture - Jurnal Ilmu Pertanian, 2024)
Sorghum (Sorghum bicolor L) is a versatile plant that can be used as a food source, animal feed and industrial raw materials. The main problems of sorghum development in Adonara District, especially in Sago Village, are the low comparative and competitive advantage value of sorghum, post-harvest handling is still difficult, and sorghum farming at the farmer level has not been intensified. This study aims to determine the response of farmer group members to the development of sorghum plants. The method used in this study is a survey method with a quantitative approach. The sample used was a saturated sample of 30 people, and the data analysis used a Likert scale and multiple linear regression. The results showed that the response as motivation (X1) with an average score of 4.23, the response as perception with an average score of 4.06, the response as a behavior with an average score of 4.13 and the development of sorghum (Y) with an average score of 4.72. The F test counted 19,415 and T test count 10,715 With this, it can be concluded that the response as motivation, perception and behavior of farmers has a significant influence on the development of sorghum